SOCIALLY RESPONSIBLE INVESTMENT SEBAGAI MOTIF PENERAPAN SUSTAINABLE CORPORATE SOCIAL RESPONSIBILITY - Vera Intanie Dewi (Center for Economic Studies Universitas Katolik Parahyangan, 2012)
Socially responsible investment (SRI) usually known as sustainable or ethical or green investment is a new type of investment movement in response to social expectations of investors. Social investors are people who want to improve conditions in society by investing their money in shares or mutual fund from companies that doing their practices in environmental, social and governance issues. Thus, SRI is investing that is mindful of the impact on environmental and society of that investment. It is often described to investors as allowing them